Analysis of CD39/ATP Diphosphohydrolase (ATPDase) Expression in Endothelial Cells, Platelets and Leukocytes - Koziak, Katarzyna; Sévigny, Jean; Robson, Simon C.; Siegel, Jonathan B.; Kaczmarek, Elzbieta (Thrombosis and Haemostasis, 1999)
Purinergic signaling may influence hemostasis, inflammatory responses and apoptosis. Therefore, hydrolysis of extracellular ATP and ADP by the ATP diphosphohydrolase (ATPDase) could regulate these processes. We have previously demonstrated the identity between the vascular ATPDase and CD39. Here we show that levels of CD39 expression correlate with ATPDase activity in human endothelial cells (EC), platelets and selected monocyte, NK, and megakaryocyte cell lines. Western blotting revealed one to three isoforms of CD39/ ATPDase; mobility variations of major protein resulted from post-translational modifications. Northern blotting and primer extension indicated two major mRNA transcripts and one transcription start point, respectively. In addition, mRNAs specific for purinergic P2 receptors were detected in all of the investigated cells, suggesting that the co-expressed CD39/ATPDase may regulate purinergic signaling. Thrombotic and inflammatory responses may be modulated by the expression of CD39/ATPDase.